Walk the walk: how three police chiefs defied the odds and changed cop culture - Gross, Neil (Metropolitan Books, 2023)
"From "one of the most interesting sociologists of his generation" and a former cop, the story of three departments and their struggle to change aggressive police culture and achieve what Americans want: fair, humane, and effective policing"--